Conditions of Correctional Facilities in the Philippines: Jail Wardens’ Perspectives and Experiences - Van Ryan Icalina Alipoyo (Department of Government Studies Universitas Muhammadiyah Makassar, 2022)
The study explored the perspective and experiences of jail wardens in managing jail facilities in the Philippines for the calendar year 2019. A qualitative study with a transcendental phenomenological research design was used. The study focused on 10 jail wardens from correctional facilities in the provinces of Zamboanga del Norte and Zamboanga del Sur, Philippines. The themes reflect the participants' experiences on the conditions of correctional facilities and their viewpoint on quality correction such as erosion in conformity with the rules, scarcity of resources critical to jail services, the perils of poor staffing, freedom from congestion, infrastructure development, technology in correction, lifelong attempt for improvement and character development. This study concluded that the problems and challenges encountered by the correctional wardens in handling persons deprived of liberty (inmates) and in managing the jail facilities affected their roles and responsibilities in improving the conditions in the correctional facilities such as in the implementation of the reformation process of the PDLs, peace, and order within the facility, and in securing the safety of the personnel and the community. Thus, it is high time for the government and the legislative body of the Philippine government to improve the quality of correctional facilities, the following may be considered: the installation of high technology, construction of new and standard correctional facilities, and quick rehabilitation of old, outdated, or destroyed jails, allocation of budget or appropriations to enable the employment of more staff/personnel, and limiting the number of inmates in a prison cell.